Public Smoking Bans, Youth Access Laws, and Cigarette Sales at Vending Machines - Michael Kvasnicka (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
Tobacco control policies have proliferated in many countries in recent years, in particular youth access laws and public smoking bans. The effectiveness of youth access laws is still disputed, however, as are the costs of public smoking bans to the hospitality industry. Using a unique data set on cigarette sales at more than 100k vending machines that provides first objective evidence on the outgoing and customer behavior of smokers, we study both outcome dimensions by investigating several recent tobacco control measures in Germany. We find a large negative effect on cigarette sales of a nation-wide introduction of devices for electronic age verification in cigarette vending machines, particularly at machines placed outdoors and in localities that are strongly frequented by youths. In contrast, there is no evidence that a country-wide smoking ban in federal buildings affected cigarette sales in these premises and only weak evidence that a recent rise in the minimum legal smoking age affected cigarette purchases by youths. Finally, state-level smoking bans appear to have reduced indoor sales of cigarettes at vending machines, especially in bars. However, the magnitude of the estimated effect is rather modest, suggesting that businesses in the hospitality industry are unlikely to have been affected severely. – – Das vorliegende Papier untersucht anhand von Umsatzdaten an Zigarettenautomaten die Wirkungen von vier verschiedenen Maßnahmen zur Kontrolle bzw. Begrenzung des Zigarettenkonsums in Deutschland: die elektronische Alterskennung an Automaten (Januar 2007), die Anhebung des Mindestalters für den Erwerb und Konsum von Zigaretten von 16 auf 18 Jahren (September 2007), das Rauchverbot in Einrichtungen des Bundes (ebenfalls September 2007) sowie Rauchverbote in der Gastronomie auf Länderebene (zwischen August 2007 und Juli 2008). Die Ergebnisse zeigen einen starken Rückgang des Zigarettenabsatzes an Automaten in Folge der Einführung der elektronischen Alterskennung, besonders an Automaten im Außenbereich und in Einrichtungen, die stark von Jugendlichen frequentiert werden. Im Gegensatz findet sich jedoch keine Evidenz dafür, dass das Rauchverbot in Einrichtungen des Bundes zu einem Rückgang des Absatzes an Zigarettenautomaten in diesen Einrichtungen geführt hat. Auch gibt es nur schwache Evidenz für einen Einfluss der Anhebung des Mindestalters auf den Erwerb von Zigaretten durch Jugendliche. Rauchverbote auf Bundeslandebene hingegen haben den Zigarettenabsatz an Automaten im Innenbereich reduziert, besonders in Kneipen. Die moderate Größe dieses Effektes legt jedoch den Schluss nahe, dass Gastronomiebetriebe durch die Rauchverbote keine starken Umsatzeinbußen erfuhren.
Keywords: I18; K32; L51; 330; Smoking; tobacco control; youth and second-hand smoking; hospitality industry; Rauchen; Jugendschutz; Wirkungsanalyse; Zigarette; Automat; Umsatz; Deutschland